UZBEK LEXICOGRAPHY (Web of Teachers: Inderscience Research, 2024)
The history of the Uzbek people, whose cultural development began in the millennia BC, is an integral part of the world history and the development of human society. In our old country, one of the cradles of world civilization, which gave birth to geniuses, along with the reforms being carried out in the field of social renewal, special attention is being paid to raising spirituality. one of the main reasons is the universalization of today's processes, in an era of increased falsification of national values, having communicative competence, communication culture is one of the important indicators of a modern person.